2018
DOI: 10.3390/app8050790
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Antimony-Germanate-Borate Glass Fibers Doped with Eu3+ Ions with Self-Assembling Silver Nanoparticles for Photonic Applications

Abstract: In the authors' opinion, and based on a literature survey, the developed and characterized SGB glass fibers with self-assembling silver nanoparticles can be applied in special SERS biosensors. Due to a simple and inexpensive method of silver nanoparticle creation on the surface of fabricated glass fibers, it is possible to use our glass fiber as the active part of multifunctional nanosystems for biophotonic measurements at the molecular level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…enabling effective light control. Recently, many novel photonic materials have combined two glass-forming elements with relatively different phonon energies: antimony-borate [8,9], lead-germanate [10,11], lead-phosphate [12,13], germanate-bismuth [14,15], or antimony-phosphate [16,17]. It is evident that this approach allows transparent and thermally stable glass to be achieved, which is useful in optical fiber fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…enabling effective light control. Recently, many novel photonic materials have combined two glass-forming elements with relatively different phonon energies: antimony-borate [8,9], lead-germanate [10,11], lead-phosphate [12,13], germanate-bismuth [14,15], or antimony-phosphate [16,17]. It is evident that this approach allows transparent and thermally stable glass to be achieved, which is useful in optical fiber fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…Going on further, Zmojda et al presented the synthesis of antimony borogermanate-based glasses which contain the same NPs and ions as the previous work. 35 The conclusion of this study shows that there is an increase of 36% in the emission at 616 nm as the time of the annealing procedure increases. The authors also proposed a bottom-up approach for the synthesis of AgNPs on glass fibers, based on the reduction of Ag + cations from the inside part of the glass towards the surface.…”
Section: Composite Glasses and Related Applicationsmentioning
confidence: 71%
“…It has to be mentioned that the concentration of silver ions plays an important role in this process, as for low concentrations there were AuNPs observed on the surface of the developed fibers. 35 Vijayakumar et al reported on borophosphate glasses containing AgNPs as before, while being doped with Eu 3+ ions. 36 The obtained emission features revealed an enhancement in the luminescence intensity, while the composite glasses were capable of emitting red light by 405 nm excitement.…”
Section: Composite Glasses and Related Applicationsmentioning
confidence: 94%